2009
DOI: 10.1186/1756-9966-28-159
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α gene polymorphisms and cancer risk: a meta-analysis

Abstract: BackgroundThe results from the published studies on the association between hypoxia-inducible factor -1α (HIF-1α) polymorphisms and cancer risk are conflicting. In this meta-analysis, we aimed to investigate the association between HIF-1α 1772 C/T and 1790 G/A polymorphisms and cancer.MethodsThe meta-analysis for 1772 C/T polymorphism included 4131 cancer cases and 5387 controls, and for 1790 G/A polymorphism included 2058 cancer cases and 3026 controls. Allelic and genotypic comparisons between cases and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…For the HIF-1α C1772T polymorphism, however, no statistically significant associations were found with digestive cancer risk, indicating that the C1772T, which may result in an amino acid change from proline 582 to serine, could not change HIF-1α expression, and therefore, it was not the primary determinant of carcinogenesis in the digestive system. Previous studies have shown that the polymorphic allele of C1772T polymorphism was associated with increased breast cancer risk, but such association was not found in other cancers (Kim et al, 2008;Zhao et al, 2009). Our findings are partially consistent with the previous hypothesis that variability in the HIF-1α gene may alter the susceptibility to digestive cancers, and these polymorphisms may be useful as biomarkers in predicting cancer development.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For the HIF-1α C1772T polymorphism, however, no statistically significant associations were found with digestive cancer risk, indicating that the C1772T, which may result in an amino acid change from proline 582 to serine, could not change HIF-1α expression, and therefore, it was not the primary determinant of carcinogenesis in the digestive system. Previous studies have shown that the polymorphic allele of C1772T polymorphism was associated with increased breast cancer risk, but such association was not found in other cancers (Kim et al, 2008;Zhao et al, 2009). Our findings are partially consistent with the previous hypothesis that variability in the HIF-1α gene may alter the susceptibility to digestive cancers, and these polymorphisms may be useful as biomarkers in predicting cancer development.…”
Section: Discussionsupporting
confidence: 82%
“…Increased HIF-1α expression could occur in the early stages of carcinogenesis, before histological evidence of angiogenesis or invasion can be available (Mabjeesh and Amir, 2007). Therefore, it is biologically plausible that genetic variations of the HIF-1α gene may contribute to individual cancer susceptibility as genetic modifiers of cancer risk (Zhao et al, 2009). The HIF-1α gene has been mapped to locus 14q21-q24.…”
Section: Discussionmentioning
confidence: 99%
“…While the recessive model (TT versus CT/CC) was significantly associated with resistance to ADT, the dominant (TT/ CT versus CC) and additive models were significant for metastasis development under ADT. A recently published meta-analysis suggests that both the T allele and TT genotype were significantly associated with increased cancer risk [17]. Experimental data also support a functional role for the C-by-T substitution at the allele and homozygous genotype level [12,28,29].…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies yielded conflicting results regarding the involvement of HIF1A +1772 C>T genetic polymorphism in cancer, albeit a significant positive association remained after meta-analysis in Caucasian women specific cancers [16,17]. In prostate cancer, the few studies were conducted in distinct ethnic populations and clinicopathological characteristics leading to conflicting results [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison model through data analysis from 6 studies (2143 cases and 2046 controls studies), we showed that the C1772T polymorphism was not associated with increased breast cancer risk. Zhao et al [24] performed a meta-analysis and explored the association between the C1772T polymorphism and cancer risk including breast cancer. The showed that the C1772T polymorphism was significantly associated with higher cancer risk in breast cancer, which was not consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%